2021
DOI: 10.3390/pharmaceutics13020160
|View full text |Cite
|
Sign up to set email alerts
|

Selective Laser Sintering of Solid Oral Dosage Forms with Copovidone and Paracetamol Using a CO2 Laser

Abstract: Material suitability needs to be considered for the 3D printing of solid oral dosage forms (SODFs). This work aims to assess the suitability of a CO2 laser (λ = 10.6 μm) for selective laser sintering of SODFs containing copovidone and paracetamol. First, physicochemical characterization of powders (two grades of copovidone, two grades of paracetamol and their mixtures at various proportions) was conducted: particle size distribution, morphology, infrared absorbance, flowability, and compactness. Then, printing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 52 publications
(49 reference statements)
4
32
0
Order By: Relevance
“…Other lasers such as CO 2 lasers (10.6 µm), due to their high-power, could potentially degrade the drug or drastically modify the properties of the polymer. However, this argument can be contested as in many conventional SLS printers equipped with a CO 2 laser, the power can be modulated, unlike in the Sintratec kit where this value is kept constant at 2.3 W. This was demonstrated by a more recent work published in 2021 (not reviewed) which reports successful CO 2 laser sintering of printlets containing Copovidone and Paracetamol without degradation of the drug [ 78 ]. However, more sensitive active ingredients, such as proteinic hormones or enzymes, could be affected by the laser energy.…”
Section: Technical Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…Other lasers such as CO 2 lasers (10.6 µm), due to their high-power, could potentially degrade the drug or drastically modify the properties of the polymer. However, this argument can be contested as in many conventional SLS printers equipped with a CO 2 laser, the power can be modulated, unlike in the Sintratec kit where this value is kept constant at 2.3 W. This was demonstrated by a more recent work published in 2021 (not reviewed) which reports successful CO 2 laser sintering of printlets containing Copovidone and Paracetamol without degradation of the drug [ 78 ]. However, more sensitive active ingredients, such as proteinic hormones or enzymes, could be affected by the laser energy.…”
Section: Technical Challengesmentioning
confidence: 99%
“…Nonetheless, some well-established assays could be adapted to new technologies, in particular to SLS, since it shares the same type of materials with direct compression and granulation. Indeed, Carr index and Hausner ratio calculated from bulk and tapped densities could be good values to estimate the flowability and compactness of powders and hence assess their suitability for the SLS process [ 46 , 78 ]. Eventually, the standards will need to be readjusted to meet the specific technological requirements.…”
Section: Regulatory Requirements For the Implementation Of Slsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, when the powder contains more than one component, the heating temperature that ensures optimal printing can change, especially if the new component modifies the thermal properties of the mixture. For instance, it has been demonstrated that paracetamol can reduce the heating temperature of the sintering process due to its plasticizing effect [ 17 ]. Similar observations were made in hot-melt extrusion (HME) [ 18 ] and fused deposition modelling (FDM) [ 19 ], where the introduction of plasticizers or even active pharmaceutical ingredients (APIs) decreased the extrusion and printing temperatures by reducing the melt viscosity of the formulation.…”
Section: Introductionmentioning
confidence: 99%
“…Formulation of solid oral dosage forms with different 3D printing methods mainly affect features such as drug release, mechanical properties, and external appearance. FDM and related techniques have been used for a wide range of applications and allowed the manufacturing of variously engineered solid dosage forms [9][10][11][12], while SLS has been investigated for its power to fabricate rapidly disintegrating tablets [13][14][15][16][17]. SLA and DLP 3D printing have been instead used to fabricate controlled release dosage forms, hydrogels and polypills [7,[18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%